Human resource activities of Beximco Pharmaceuticals Limited (BPL) Bangladesh - Alam, Mashfa Binte (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.